Prenatal Care for Adolescents and attributes of Primary Health Care - Maria Cristina Barbaro; Angelina Lettiere; Ana Márcia Spanó Nakano (Universidade de São Paulo, 2014)
OBJECTIVE: evaluate prenatal care for adolescents in health units, in accordance with the attributes of Primary Health Care (PHC) guidelines. METHOD: quantitative study conducted with health professionals, using the Primary Care Assessment Tool-Brazil to assess the presence and extent of PHC attributes. RESULTS: for all the participating units, the attribute Access scored =6.6; the attributes Longitudinality, Coordination (integration of care), Coordination (information systems) and Integrality scored =6.6, and the Essential Score =6.6. Comparing basic units with family health units, the attribute scores were equally distributed; Accessibility scored =6.6, the others attributes scored =6.6; however, in the basic units, the Essential Score was =6.6 and, in the family health units, =6.6. CONCLUSION: expanding the coverage of family health units and the training of professionals can be considered strategies to qualify health care.